Thermodynamic analysis of adsorption cooling cycle using consolidated composite adsorbents - ethanol pairs - Pal, A. (Asian Research Publishing Network, 2016)
This study deals with the thermodynamic analysis of adsorption cooling cycle using consolidated composite adsorbents-ethanol pairs. The studied composites are named as composite A (50 Maxsorb III, 40 expanded graphite (EG), 10 binder) and composite C (70 Maxsorb III, 20 expanded graphite (EG), 10 binder). The Dubinin-Radushkevich (D-R) and Dubinin Astakhov (D-A) equation are used to draw pressure-temperature-concentration (P-T-W) diagrams of the assorted pairs. The specific cooling effect (SCE) and coefficient of performance (COP) of both pairs have been simulated for desorption temperatures ranging from 40 to 90 °C at different evaporator temperatures along with a heat sink at 30 °C by considering a time independent thermodynamic model. The maximum COPs of composite A-ethanol and composite C-ethanol based cooling systems are found to be 0.69 and 0.765, respectively. ©2006-2016 Asian Research Publishing Network (ARPN).